The falling in love with the brand: A study on automotive products - Yusniar, .; Permana Honeyta Lubis, Jasman. J. Ma’ruf, Sulaiman,; Saputra, Jumadil (Opción, 2019)
This study is written to investigate the relationship between antecedents (favorability, strengthens, and uniqueness of brand love) and subsequently, its impact on brand loyalty. A total of 400 respondents were participated and collected using purposive sampling. It should be noted that the sample considered meets with the appropriate characteristics. The result shows that the strength and excellence that exist in the brand (brand image) will lead consumers to a sense of happiness (love) towards the brand, and it subsequently generates brand loyalty.